2023
DOI: 10.15586/qas.v15i1.1234
|View full text |Cite
|
Sign up to set email alerts
|

Wogonoside improves high-fat diet-induced hyperlipidemia and aortic injury in ApoE -/- mice by upregulating SIRT1 expression

Abstract: This study aimed to evaluate the effect of Wogonoside (Wog), a flavonoid monomer, on hyperlipidemia and explore its possible mechanisms. APOE -/- mice were used to establish the animal model of hyperlipidemia by feeding the high-fat diet (HFD). The serum level of triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), and inflammatory cytokines were measured by enzyme-linked immunosorbent assay (ELISA), oil red O staining, and real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Subsequent biological investigations confirmed the regulatory effects of these five screened compounds on lipid metabolism. In addition, existing research results have also shown that all screened effector molecules have regulatory effects on lipid metabolism, thus verifying the effectiveness of this method in selecting potential CPT1A-targeted bioactive compounds from traditional Chinese medicine. This method is characterized by its convenience, stability, reliability, high efficiency, and sensitivity, making it highly suitable for screening active substances in traditional Chinese medicine or multicomponent systems.…”
Section: Discussionmentioning
confidence: 77%
“…Subsequent biological investigations confirmed the regulatory effects of these five screened compounds on lipid metabolism. In addition, existing research results have also shown that all screened effector molecules have regulatory effects on lipid metabolism, thus verifying the effectiveness of this method in selecting potential CPT1A-targeted bioactive compounds from traditional Chinese medicine. This method is characterized by its convenience, stability, reliability, high efficiency, and sensitivity, making it highly suitable for screening active substances in traditional Chinese medicine or multicomponent systems.…”
Section: Discussionmentioning
confidence: 77%